Pengaruh Kecepatan, Maintanance, Ketelitian dan Strategi Pemasaran terhadap Kepuasan Pelanggan pada CV Andi Jaya Technology - Ita Fiani; Septa Diana Nabella; Amirullah Amirullah (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2025)
Customer satisfaction is a key factor in the success of a company, especially in the technology industry that demands fast, accurate, and quality service. This study aims to analyze the effect of Speed, Maintenance, Accuracy, and Marketing Strategy variables on Customer Satisfaction at CV. Andi Jaya Technology. The research method used is regression analysis with t-test to measure the effect of each variable partially and F-test to see the effect simultaneously. The results of the study show that partially, the Speed ​​variable has a t-count value of 4,352, Maintenance of 5,573, Accuracy of 6,167, and Marketing Strategy of 3,166. All t-count values ​​are greater than t-table (1,677 at α = 5%), so it can be concluded that each variable has a significant effect on Customer Satisfaction. In addition, the results of the simultaneous test show that the variables Speed, Maintenance, Accuracy, and Marketing Strategy together have a significant influence on Customer Satisfaction with an F-count value of 9.515, greater than the F-table (2.58 at α = 5%). The results of this study confirm that factors such as speed of service, system maintenance, accuracy in work, and effective marketing strategies play an important role in increasing customer satisfaction. Therefore, CV. Andi Jaya Technology needs to continue to improve these aspects in order to maintain customer loyalty and increase the company's competitiveness in the technology industry.